Short-term effects of agricultural practices on the soil structure and hydrodynamic in a deep tilled hardened sandy-silty volcanic–ash soil (cangahua) in Ecuador - Podwojewski, Pascal; Janeau, Jean L. (2005)
In the Ecuadorian Cordillera, the hardened volcanic ashes (cangahuas) account for 15% of the cultivated area. The soil resulting from the fragmentation of these materials, generally by heavy machinery, shows an apparent stable millimetric structure. However, this new structure is highly susceptible to disintegration under rain, because it contains no organic matter and has a sandy-silt composition with very little mineralogical clay, and the material itself is readily eroded. In consequence we studied the evolution of soil aggregate stability in two factorial experiments during five cultivation cycles with two kinds of soil preparation and five fertilization treatments. Rainfall simulation was implemented before and after three cycles of cultivation to asses the soils structure evolution and its erodibility. The cultivated plots had flat surfaces and the rainfall simulation tests were conducted after the harvest on bare surfaces. Surface soil crusting occurred rapidly within the cultivated plots when compared to the recent tilled cangahua. Runoff and soil loss were generally higher on plots with lower structural stability, generally with higher clay content. The aggregate stability was not influenced by either kind of soil preparation, nor by large additions of manure (80 t ha-1) or green fertilizers (10 t ha-1), nor by growing a perennial grass. The variation in the aggregate stability seemed to depend on the components inherited from the original volcanic material: in the plots with larger clay content, and with swelling clay minerals, the aggregates were less stable than those composed of isometric fine silt particles. In agreement with the structural stability measured in a laboratory, organic matter inputs increase the soil porosity but had no effect on the structural stability and resistance to crusting, and thus to runoff and to erosion. For these soils, no tillage and a permanent soil cover (pasture) would be the best agricultural option.